2022
DOI: 10.1049/ipr2.12449
|View full text |Cite
|
Sign up to set email alerts
|

New fully automatic approach for tissue identification in histopathological examinations using transfer learning

Abstract: The use of computational techniques in the processing of histopathological images allows the study of the structural organization of tissues and their changes through diseases. This study aims to develop a tool for classifying histopathological images from breast lesions in the benign and malignant classes through magnification scales by an innovative way of using transfer learning techniques combined with machine learning methods and deep learning. The BreakHis dataset was used in the experiments, consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 52 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…The World Health Organization (WHO) [1] reported that cancer is a major cause of death worldwide, with an estimated 10 million deaths due to the disease in 2020. Unchecked growth and the development of cancerous cells are caused by genetic mutations in cells, which are distinguished by alterations in their DNA [2].Out of all the cancers that affect populations worldwide, breast cancer is the most common type among women [3].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) [1] reported that cancer is a major cause of death worldwide, with an estimated 10 million deaths due to the disease in 2020. Unchecked growth and the development of cancerous cells are caused by genetic mutations in cells, which are distinguished by alterations in their DNA [2].Out of all the cancers that affect populations worldwide, breast cancer is the most common type among women [3].…”
Section: Introductionmentioning
confidence: 99%